P.103 Midline Spikes and Intractable Seizures in Pediatric Epilepsy. (November 2021) - Luan, K; Mailo, J; Liu, N; Kassiri, J; Sinclair, DB
Abstract : Background: Epileptic discharges localized to the midline vertex are rare. However, they have been associated with intractable seizures and severe long-term consequences in the developing brain. Our study aimed to understand the etiology of pediatric midline seizures and define post-surgical seizure outcomes. Methods: We reviewed charts, electroencephalography (EEG), and neuroimaging studies of ten pediatric patients with epileptic discharges localized to the midline vertex in the Comprehensive Epilepsy Program. The seizures were classified according to the International League Against Epilepsy criteria, patient age, sex, neuroimaging results, seizure etiology and outcomes were obtained. Results: Age of seizure onset was within the first 10 years of life in 90% of patients, with focal seizures being the most prevalent. Focal cortical dysplasia (FCD) was the most common etiology present in 50% of patients. These children had normal neuroimaging studies and intractable epilepsy. However, seizure freedom was achieved following surgical resection of the epileptogenic zone. Conclusions: We demonstrated that patients with midline epileptic discharges are associated with intractable focal seizures and early seizure onset. Despite normal neuroimaging reports, FCD was the most common pathology. Thus our study suggests early localization and resection of the epileptogenic zone may be beneficial for achieving seizure freedom in children with this electroclinical syndrome.